4 - L’université, un outil de développement local ? Le cas de Jendouba en Tunisie - Dhaher Najem, (Journal of Higher Education in Africa, 2012)
Since the beginning of 1990s, the Tunisian university knew reforms which totally upset his landscape. The explosion of the student staff was accompanied by a remarkable real estate development. In two decades, the number of students increased in a vertiginous way what contributed to the massification of the higher education. This phenomenon modified the geography of the university spaces and favored a redistribution of the teachings. Mid-sized cities, held up to here away from the university presences, are gradually endowed with this new function. The investigations show that the university in certain mid-sized cities is a precursor of important changes. It generates a more located and structuring impact for the urban zones where it is implanted and shines on a vast territory regional as the geographical areas of recruitment of the students illustrate it. After more than a decade on the presence of the university campus in the city of Jendouba, we begin to discover to the local level the assets of the higher education, evoked in terms of urban dynamics and socioeconomic and cultural potentialities. We suggest here presenting the characteristics of this urban developer in future from this study case in Tunisia.